PENGGUNAAN MEDIA AUDIO VISUAL TERHADAP KETUNTASAN BELAJAR IPS MATERI PERKEMBANGAN TEKNOLOGI PRODUKSI, KOMUNIKASI, DAN TRANSPORTASI - Fitriana, Fitriana (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2019)
This study, entitled "The use of audio visual media on social studies completeness in the development of production, communication, and transportation technology for fourth grade students" raises the issue of whether the use of audio-visual media can achieve completeness in social studies learning material development of production technology, communication, and transportation in the classroom. IV. This study aims to determine students' learning completeness using audio-visual media on the development of communication and transportation technology materials. The population in this study were all fourth grade students, totaling 51 students. The sample in this study was 26 students of class IV A for the 2020-2021 academic year. The approach used in this research is a quantitative approach, with the type of research is quasi experiment. The data was collected by means of tests. Study result test data, especially the material for the development of production, communication and transportation technology. The value obtained is what is taken as data. Then the data is processed using the percentage formula. The mean score of the students' test results was 82.41. Students who complete learning are 92%, namely 24 students and students who complete 8% are 2 students. Thus it can be concluded that the use of the use of audio visual media on the completeness of learning Ips material for the development of production, communication and transportation technology in grade IV students can achieve complete learning outcomes.